Investigação geofísica em aterro municipal de resíduos sólidos domiciliares, Cordeirópolis, Brasil - Moreira, César Augusto [UNESP]; Braga, Antonio Celso de Oliveira [UNESP]; Martinelli, César D'Abronzo (My University, 2013)
This paper presents the results of the Electrical Resistivity geophysical method in the evaluation of leachate percolation in soil, originated from decomposition of organic matter contained in domestic solid waste. The landfill system operation consists basically in five meters deep ditch excavation, daily deposition of 7m3 of domestic solid waste from a city with 17.000 inhabitants and subsequent cover by soil removed during ditch excavation. Absence of ditch waterproofing and of gas and liquid collection systems, justify the application of geophysics in the characterization and monitoring of the percolated flux in soil and groundwater. The occurrence of resistivity values below 30Ω.m in the results and the absence of this range in the reference line, coupled with the presence of high total dissolved solids in the liquid derived from organic matter decomposition, reveal leachate concentration zones in soil. This range of values has been described in diverse geophysical investigations carried out in solid waste landfills in the Brazilian Southeast region, notably characterized by thick soil layers and variable clay and sand content.

Este trabalho apresenta os resultados do método geofísico da Eletrorresistividade na avaliação de lixiviado percolado em solo, proveniente da decomposição de matéria orgânica contida em resíduos sólidos domiciliares. O sistema de operação do aterro consiste basicamente na escavação de valas com cinco metros de profundidade, deposição diária de 7m3 de resíduos sólidos domiciliares provenientes de um município de 17 000 habitantes e posterior cobertura pelo solo retirado durante a escavação das valas. A ausência de impermeabilização das valas ou de sistemas de coleta de gases e líquidos, justificam a aplicação da geofísica na caracterização e monitoramento do fluxo de percolados no solo e águas subterrâneas. A ocorrência de valores de resistividade inferiores a 30Ω.m nos resultados e ausência desta faixa de valores na linha de referência, aliado a característica de elevada quantidade de sólidos totais dissolvidos no líquido proveniente da decomposição da matéria orgânica, revelam zonas de concentração de chorume no solo. Esta faixa de valores foi descrita em diversas investigações geofísicas realizadas em áreas de aterros de resíduos sólidos na região Sudeste do Brasil, notadamente caracterizadas por solos espessos e teores variáveis de argila e areia.
Geophysical investigation in municipal solid waste landfill, Cordeirópolis, Brazil
Keywords: Aterro sanitário; Chorume; Geofísica; Resistividade elétrica